Long‐term outcomes of endoscopic submucosal dissection for early gastric cancer: A single‐center retrospective study. Issue 2 (7th April 2013) - Kosaka, Takashi; Endo, Masaki; Toya, Yosuke; Abiko, Yukito; Kudara, Norihiko; Inomata, Masaaki; Chiba, Toshimi; Takikawa, Yasuhiro; Suzuki, Kazuyuki; Sugai, Tamotsu
<x xml:space="preserve">Abstract</x> Background The aim of the present study was to examine the safety and efficacy of endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) based on the long‐term outcomes. Patients and Methods From June 2002 to March 2007, ESD was carried out in 472 cases and 570 lesions of EGC. Post‐surgical cases and status‐unknown cases were excluded. The following long‐term outcomes were examined in 438 patients who were reliably followed up for at least 5 years after treatment (range: 5 years [60 months] to 9 years, 9 months [117 months]): local recurrence, metachronous recurrences, and the survival rate. Results The overall en bloc resection rate was 97.7% for all lesions treated by ESD. The median procedure time was 47.0 min (range 8–345 min). The incidence of positive horizontal andvertical margins was 3.7% and 3.4%, respectively. The incidence of perforation and postoperative bleeding was 5.3% and 4.3%, respectively. There were no deaths related to ESD. Local recurrence was observed in five patients (1.1%), and metachronous recurrences in 7.8% of the patients. The post‐treatment 5‐year survival was 83.1%. There were no deaths as a result of gastric cancer associated with sites treated by ESD. Conclusion ESD can be considered a standard treatment for EGC based on its expanded indications and low incidences of local recurrence and lymph node metastasis.